Normal and convergent methods of survey for inventory and certification of cultural structures - Hubar, Yurii; Sai, Vira; Кhavar, Yulia; Vynarchyk, Liliya; Hulko, Oleksandra (Geodesy and Cartography, 2023)
The article aims to study the use of normal and convergent stereo-photographic techniques to determine physical condition of a building, to compare errors obtained using a digital non-specialized camera, and use these methods in the inventory and certification of real estate. Monitoring architectural monuments is currently one of the most urgent problems. The development of large cities in which architectural monuments are under threat of destruction requires modern and effective technology for monitoring which is possible using low-cost photogrammetry methods: digital images and cheap software. The development of digital cameras into terrestrial photogrammetry resulted in fundamentally new methods and photogrammetric technologies. In case of monitoring objects of small sizes, such as architectural monuments, the cost of shooting equipment is one of the most significant factors, which reduces the cost of work, therefore, in the vast majority of cases, only digital non-metric cameras are used for shooting. The most significant problem is the calibration of digital non-metric cameras. Currently, a huge number of options for calibrating digital cameras have been developed. These options differ in calibration method, type of test object, type of mathematical model for accounting for distortion (algebraic, physical or hybrid model) The present study how that accuracy of the convergent method is almost 2 times higher than that of the normal photogrammetric survey method and provides a large survey overlap area. Comparing all the indicators and characteristics of these methods, we concluded the feasibility, high profitability, and low complexity of the convergent method of stereo photography to perform inventory and certification of real estate. We found that when surveying building using convergent method it is necessary to use 2 times fewer stations than when surveying by normal method. Thus, the convergent method is 2 times faster and more efficiently.